Pre-service teachers' (cohort 9) lived experiences related to English native assistant's support in a foreign language teaching education program at UCO (2019)
The purpose of this paper is to evidence students’ voices through their lived experiences related to native English assistants in a private university in Colombia. research journals, semi-structured interviews and surveys. One of the problems we faced when developing the project was the disposition of students to participate in the interviews and surveys proposed to gather information. During the analysis of the findings, it was evidenced the discontent that students had with the performance of the English native assistants inside the classroom. Although students thought that the strategy of bringing assistants to the classroom is good, it is notorious that those assistants should have previous knowledge about pedagogy in order to be clearer when supporting a class. To conclude, it was necessary to evidence students’ voices as a tool to have an overall view about how the process have been carrying out until this moment. In order to do so, the project was conducted using systematization of experiences, additionally, three data collection methods were used to evidence students’ voices.